2023
DOI: 10.1111/papt.12492
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an optimal working relationship with patients with an antisocial personality disorder. Aspects and processes in the therapeutic alliance

J. E. M. Aerts,
M. J. N. Rijckmans,
S. Bogaerts
et al.

Abstract: ObjectiveDeveloping good interpersonal relationships is one of the main impediments for people with an antisocial personality disorder (ASPD). However, in treatment of psychiatric disorders, establishing a strong therapeutic alliance (TA) is important for effective treatment. Nevertheless, there is little knowledge on how to establish this TA with this challenging patient group. This study investigates which factors are important in TA development.MethodFor this study, a qualitative research methodology is app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…It appears to be particularly difficult to establish a good working alliance with individuals with ASPD, primarily because of treatment-rejecting behavior and characteristics that affect the therapeutic relationship negatively. However, recent studies have identified factors related to establishing a positive therapeutic alliance such as tailoring the treatment, being attentive, authentic and non-judgmental, together with maintaining a firm stance or uphold boundaries ( Morken et al, 2022 ; Aerts et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It appears to be particularly difficult to establish a good working alliance with individuals with ASPD, primarily because of treatment-rejecting behavior and characteristics that affect the therapeutic relationship negatively. However, recent studies have identified factors related to establishing a positive therapeutic alliance such as tailoring the treatment, being attentive, authentic and non-judgmental, together with maintaining a firm stance or uphold boundaries ( Morken et al, 2022 ; Aerts et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term consequences may include increased burnout rates, as shown in forensic mental healthcare workers (3)(4)(5). Apart from adverse consequences for healthcare workers, transgressive behavior can hinder therapeutic progress of the patient, potentially prolonging treatment due to disruptions in the clinical atmosphere (e.g., revocation of privileges) and/or the induction of fear and stress among professionals (6,7). Hence, preventive measures are needed (1,8).…”
Section: Introductionmentioning
confidence: 99%